Critical illness myopathy: What is happening? - Friedrich, Oliver (Current Opinion in Clinical Nutrition and Metabolic Care, 2006)
PURPOSE OF REVIEW: The current review focuses on recent studies, both clinical and from basic sciences, which approach possible pathomechanisms of critical illness myopathy in order to better derive potential clinical strategies for a preventive or curative clinical setting. Trends and concepts of clinical diagnosis and handling will be evaluated and their implications for muscle physiology and nutritional/metabolic intervention discussed. RECENT FINDINGS: Conventional electrophysiology was combined with direct muscle stimulation to better differentiate critical illness myopathy from other neuromuscular disorders in critical illness. Muscle weakness was the result of impaired excitation-contraction-coupling at the level of the sarcolemma and the sarcoplasmic reticulum membrane. Critical illness may alter sodium and ryanodine receptor calcium-release channels. Also, increased muscle proteolysis contributes to weakness in critical illness myopathy. Myosin loss is due to the risk factors systemic inflammatory response syndrome/sepsis, steroids and neuromuscular blocking agents. Steroids can also induce necrosis and apoptosis in muscle. Inflammatory mediators aggravated muscle metabolic failure in critical illness myopathy. Ubiquitin-proteasome pathways, cyclooxygenase activation, altered glucose transporter expression, MyoD suppression, impaired respiratory chain enzymes, ATP depletion, glucose toxicity and insulin resistance can all contribute to the critical illness myopathy pathomechanism. SUMMARY: The search for pathomechanisms is an important task for both clinical and basic sciences. Targets for treatment or prevention of critical illness myopathy include systemic inflammatory response, increased proteolysis and reduced antioxidative capacitance in critically ill patients. © 2006 Lippincott Williams & Wilkins.
Keywords: Critical illness; Ec-coupling; Myopathy; Pathomechanism; SIRS; Steroids; Ubiquitin